2021
DOI: 10.1016/j.thromres.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anemia on clinical outcomes in venous thromboembolism: Results from GARFIELD-VTE

Abstract: Clinical characteristics and outcomes of venous thromboembolism (VTE) patients with concomitant anemia are unclear. This study compares baseline characteristics, treatment patterns, and 24-month outcomes in patients with and without anemia within GARFIELD-VTE. Materials and methods: GARFIELD-VTE (ClinicalTrials.gov: NCT02155491) is a global, prospective, noninterventional registry of real-world treatment practices. Of the 10,679 patients enrolled in GARFIELD-VTE, 7698 were eligible for analysis. Primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…Such findings confirm what was recently reported by a meta-analysis of all trials investigating direct anticoagulant use for VTE treatment [ 19 ], although the follow-up in the latter was limited to 12 months. They are also in line with observations from the RIETE Registry, although in patients treated only with VKA [ 15 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Such findings confirm what was recently reported by a meta-analysis of all trials investigating direct anticoagulant use for VTE treatment [ 19 ], although the follow-up in the latter was limited to 12 months. They are also in line with observations from the RIETE Registry, although in patients treated only with VKA [ 15 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…A large scale research with a real-world populations demonstrated that VTE patients (comprising 38.9% PE patients and 61.1% deep venous thromboembolism patients) with anemia faced a higher risk of all-cause mortality and major bleeding, and severe anemia was related with a larger risk of adverse outcomes. [15] Besides, the study with the multicentre registry in China also screened out that the anemia was one of risk factors associated with in-hospital all-cause mortality in hemodynamically stable PE patients (OR: 2.0, 95% CI: 1.3–3.0, P = .0020) though the multivariable analysis within hemodynamically unstable group excluded anemia as the independent factor. [9] Additionally, a prospective study developed an original risk score to predict early major bleeding in acute PE including anemia (defined as hemoglobin < 12 g/dL) as one of the 3 assessment items and the score proportion of anemia item was highest, which identified anemia as the most powerful prognostic factor of early major bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Reihe von Studien konnte herausarbeiten, dass Anämie ein wichtiger Prädiktor für das Auftreten von Blutungen ist. In GAR-FIELD-VTE [13], einem Real-World-Register, wurde der Einfluss von Anämie auf Blutungsrisiko und klinischen Verlauf analysiert. Es zeigt sich, dass Patienten mit Anämie ein 2,8-fach höheres Risiko für schwere Blutungen aufweisen; am häufigsten waren gastrointestinale Blutungen.…”
Section: Anämie Als Prädiktor Für Blutungenunclassified